Duodenal and pyloric web in children: Clinical presentation and management - Shailesh Solanki; Prema Menon; Shivani Dogra; Ram Samujh (Wolters Kluwer Medknow Publications, 2022)
Background: Duodenal and pyloric web (DW/PW) can present at any age, symptoms depend upon the location of the web along with the presence and size of the opening in the web. The surgical management is not straightforward always. Here, in this study, we aim to assess clinical characteristics, management, and outcome of children with DW/PW. Materials and Methodology: This was a retrospective study from 2005 to 2019, and data were collected from record registers. All children of DW/PW presented between this duration were included in this study. Results: A total of 45 patients (age range = 1 day to 11 years) included in the study, 40 had DW while 5 had PW. Seven patients were diagnosed antenatally and 20 patients had associated congenital anomalies. Most patients presented with vomiting either bilious or nonbilious. Plain X-ray was sufficient for the diagnosis in 60% of patients, the rest diagnosed on contrast study. The web excision and pyloroplasty were done for PW. The web excision and Heineke-Mikulicz type enteroplasty was the preferred surgery for DW but some patients were required Kimura's duodeno-duodenostomy. For postoperative nutrition, enteral feeding was established through the placement of a feeding tube beyond anastomosis. Ten patients died due to septicemia and associated anomalies. Four patients had a minor leak which was managed by conservative means. Four patients required redo surgery, adhesive obstruction was the most common indication. During follow-up, all 35 patients were doing well with no major complaints. Conclusion: DW/PW has different presentations as compared to other intestinal atresia and can present at any age. A contrast study confirms the diagnosis when plain X-ray is inconclusive. Associated anomalies and septicemia are the poor prognostic indicators. Postoperative enteral feeding helps in maintaining adequate nutrition and improves the outcome even in children with a minor anastomotic leak.